Edukasi Literasi Keuangan dan Investasi pada Siswa SMA (SMAN 1 Kembangbahu dan SMK Muhammadiyah 1 Lamongan) - Amrizal Imawan; Devi Febrianti; Ninik Mas'adah; Teguh Hadi Wibowo (Lembaga Yasin AlSys, 2026)
Although financial literacy and financial inclusion have been the focus of various studies and national policies, research that specifically addresses the strengthening of financial literacy, basic accounting, and early investment education among Generation Z in upper secondary education remains limited. This study aimed to evaluate the effectiveness of financial literacy, accounting, and investment outreach and training activities in improving Generation Z’s understanding and readiness for financial decision-making. A qualitative approach was employed through a community service program designed around socialization and training activities, involving 130 students from SMA Negeri 1 Kembangbahu and SMK Muhammadiyah 1 Lamongan selected using purposive sampling. Data were collected using pre-test and post-test questionnaires, observations, and worksheet evaluations, and were analyzed using qualitative descriptive analysis. The results showed an increase in students’ understanding of financial literacy, personal financial management, and the selection of legal investments aligned with their risk profiles. These findings contribute to the development of the concept of financial literacy among young people and broaden understanding of the importance of early financial education in the school context. The study concludes that implementing systematic financial literacy and investment education in secondary education is essential and recommends that schools and education policymakers integrate financial literacy into learning activities. The implications include theoretical contributions to the literature on Generation Z’s financial literacy and practical implications for educational institutions in building students’ financial readiness, while also opening opportunities for further research on the impact of financial literacy on Generation Z’s long-term financial behavior.